CRYSTAL CHEMISTRY OF MG-, FE-BEARING MUSCOVITES-2M - Brigatti M.F.; Frigieri P.; Poppi L. (My University, 1998)
Phengitic muscovite-2M 1 crystals [ (super [12]) (K (sub 0.88-0.99) Na (sub 0.01-0.09) Ca (sub 0.00-0.06) Ba (sub 0.00-0.01) ) (super [6]) (Al (sub 1.64-1.88) Fe (super 2+) (sub 0.06-0.29) Fe (super 3+) (sub 0.01-0.16) Mg (sub 0.00-0.16) Mn (sub 0.00-0.07) Ti (sub 0.00-0.06) ) (super [4]) (Si (sub 2.87-3.30) Al (sub 0.70-1.13) )(OH) (sub 1.56-2.07) F (sub 0.00-0.41) O (sub 9.91-10.25) ] from pegmatites and peraluminous granites were refined to investigate the influence of phengitic substitution on the mica structure. Single-crystal X-ray diffraction data were collected for eleven crystals in the C2/c space-group (agreement factor 2.1% < or = R obs , < or =3.9%). Tetrahedral Si and Al cation disorder was found for each sample, with the mean tetrahedral cation-oxygen distances ranging from 1.639 Aa < or ={T1-O}< or =1.647 Aa and 1.640 Aa < or ={T2-O}< or =1.646 Aa. As phengitic substitution increases, the octahedral sheet expands and requires a less distorted (more hexagonal) tetrahedral ring (7.70 degrees < or =alpha < or =11.38 degrees ) and low corrugation of the basal O plane (0.1796 Aa< or =Delta Z< or =0.2296 Aa). The electron density at the M2 site is greater than that required for the ideal muscovite-2M 1 structure, and a small excess of electron density is found in the M1 site. The inner sixfold coordination of the interlayer (A) cation is elongated along c (super *) , which is consistent with the high alpha values and the long A-O11 bond length.